Analysis of free vibrations of a plate and fluid in container = Analiza drgań własnych płyty i cieczy w zbiorniku - Kaczor, Anita; Sygulski, Ryszard (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper concerns the free vibrations of a plate in contact with a fluid in a container. The plate is supported at container walls. The analysed problem is a coupled problem of the structure-liquid type. It is assumed that the fluid is inviscid and incompressible. The side walls of the container are treated as rigid. Action of the fluid on the vibrating plate was described by the boundary integral equation. To solve it the boundary element method was used. Elements of constant type were applied. The plate mass was modelled by the masses concentrated in nodes. The plate flexibility matrix was determined using the FEM program. Numerical examples of the free vibrations of rectangular plates are solved.
Keywords: analiza drgań; drgania sprzężone; metoda elementów brzegowych; płyty; zbiorniki; boundary element method; fluid-structure interaction